The impact of climate change on the agricultural sector in Algeria - Econometric Study - - BECHEROUL, Fayssal (Journal of Excellence for Economics and Management Research, 2025)
The main objective of this study was to measure the impact of climate change indicators on the agricultural sector in Algeria during the period (2000-2021), and to achieve this goal, the estimation of the autoregressive distributed lags (ARDL) model developed by Pesaran et al. (2001), it was concluded by estimating the long-term relationship that there is a statistically significant and positive effect for each of the variables of rainfall, carbon dioxide emissions and employment development on the agricultural sector, while by estimating the short-term relationship it was concluded that there is a statistically significant and positive effect for both the variable rainfall and the variable employment rate in the agricultural sector.